FAKTOR‐FAKTOR YANG MEMPENGARUHI MINAT BELI PRODUK MAKANAN HALAL DI SURABAYA - Karina Permatasari; Dudi Anandya; Indarini (Perpustakaan Universitas Surabaya, 2021)
Abstract— The aim of this research is to show the influence of Halal Awareness, Religious Beliefs, Private Community Perception, Halal Certification and Halal Marketing on the Intention of Purchasing Halal Food Products in Surabaya. This type of research is basic research including the category of causal research and the method used in this study is quantitative research that uses data that generates numbers and conducts data collection directly to respondents. Respondents in this study were 157 respondents. Data processing in this study using SPSS software. The results in this study are independent variables namely Halal Awareness, Religious Beliefs, Private Community Perceptions, Halal Certification and Halal Marketing are positively and significantly related to the intention to purchase Halal food products in Surabaya. Keyword: Halal food products, purchase intention, Halal awareness, Halal certification Abstrak— Penelitian ini dilakukan bertujuan untuk menunjukkan pengaruh Halal Awareness, Religious Belief, Personal Societal Perception, Halal Certification dan Halal Marketing terhadap Purchase Intention produk makanan halal di Surabaya. Jenis penelitian ini ada basic research termasuk kategori dalam kausal riset dan metode pendekatan yang dilakukan dalam penelitian ini adalah kuantitatif karena menggunakan pengolahan data yang menghasilkan angka dan melakukan pengumpulan data secara langsung kepada responden. Responden dalam penelitian ini sebanyak 157 responden. Pengolahan data dalam penelitian ini menggunakan software SPSS. Hasil dalam penelitian ini adalah seluruh variabel independen yaitu Halal Awareness, Religious Belief, Personal Societal Perception, Halal Certification dan Halal Marketing berpengaruh positif dan signifikan terhadap Purchase Intention produk makanan Halal di Surabaya. Manajemen. Kata Kunci: Produk makanan Halal, Purchase Intention, Halal Awareness, Halal Certification.